D’OWL CAFÉ Sdn Bhd / Aizatul Azwa Abdullah ... [et al.] - Abdullah, Aizatul Azwa; Mohamad Izani, Muhammad Imran Syahmi; Ramlan, Nur Amirah Haziqah; Khairol Mokhtar, Nur Insyirah; Abd Malek, Nur Khadijah; Badrul Hisham, Siti Nur Qistina (2021)
D’Owl Cafe is the business that formally known as cafe. Our business is the organization business possessed by six partners. The entirety of the partners contributes a similar add up to begin the business which RM 50,000 each. To be effectively in our business the entireties of the partner have their own part and obligations. There are six capacities that oversaw by all of partners which are General Manager, Administration Manager, Marketing Manager, Operational Manager and lastly Financial Manager. The entirety of the partnership chose to open a cafe for our business since we need to give assortments coffee for our client as indicated by their requirements. These days, individuals are more concern on healthy food and meals, accordingly Café will offer these solid coffees as required supper. Other than that, our cafe gives an alternate taste of dessert which incorporates a few sound natural products. The idea of business for Café is shop parcel. We are serving the coffee and dessert in the Café. This idea of business is now renowned in Malaysia and not all that much expense. At long last, we truly hope that our item can be famous in our nation and furthermore another nation. We guarantee that we can make something else in future to give a solid treat to everybody.